Catalysts for the non-oxidative conversion of hydrocarbons to hydrogen.

JP2025506923APending Publication Date: 2025-03-13CHEVRON USA INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024551942
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-01
Filing Date
2023-03-01
Publication Date
2025-03-13

Smart Images

  • Figure 2025506923000001
    Figure 2025506923000001
  • Figure 2025506923000002
    Figure 2025506923000002
  • Figure 2025506923000003
    Figure 2025506923000003
Patent Text Reader

Abstract

The present disclosure relates to systems, methods, and catalysts for converting hydrocarbons to hydrogen. Catalysts are typically made of fused silica, quartz, glass, zeolites, Si 3 N 4 , SiC, SiC x O y (In the formula, 4x+2y=4), SiO a N b (in the formula, 2a+3b=4), BN, TiO 2 , ZrO 2 , Al 2 O 3 , CEO 2 , Nb 2 O 5 , La 2 O 3 , a perovskite, or any mixture thereof. A metal dopant is embedded in the matrix. The metal dopant includes Fe, Ni, Co, Cu, Zn, Mn, or any mixture thereof.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to systems, methods, and catalysts for the non-oxidative production of hydrogen from hydrocarbons, such as natural gas. [Background technology]

[0002] Hydrogen is one of the more important options for the clean energy of the future. Unfortunately, many commercially available technologies, such as steam methane reforming to produce hydrogen, are carbon intensive. Using carbon capture and storage can reduce the carbon footprint, but the available methods are often energy intensive. What is needed is a solution that produces hydrogen without being carbon intensive. It would be even more advantageous if such a solution were relatively energy efficient and cost efficient. Summary of the Invention

[0003] Advantageously, the present application relates to new systems, methods, and catalysts that can non-oxidatively produce hydrogen from hydrocarbons such as natural gas, solutions that are substantially less carbon intensive, energy efficient, and / or cost effective.

[0004] The present application relates in one embodiment to a catalyst for the non-oxidative conversion of hydrocarbons to hydrogen. The catalyst may be selected from fused silica, quartz, glass, zeolites, Si3N4, SiC, SiC x O y (In the formula, 4x+2y=4), SiO a N b (where 2a+3b=4), a matrix comprising BN, TiO2, ZrO2, Al2O3, CeO2, Nb2O5, La2O3, perovskite, or any mixture thereof. A metal dopant is embedded in the matrix, where the metal dopant comprises Fe, Ni, Co, Cu, Zn, Mn, or any mixture thereof. The catalyst is not the product of fusing ferrous metasilicate with SiO2 at a temperature between 500°C and 2400°C.

[0005] In another embodiment, the present application relates to a method for preparing a catalyst, the method comprising doping a matrix material with a metal, the metal comprising Fe, Ni, Co, Cu, Zn, Mn, or any mixture thereof. The matrix can be fused silica, quartz, glass, zeolite, Si3N4, SiC, SiC x O y (In the formula, 4x+2y=4), SiO a N b (where 2a+3b=4), BN, TiO2, ZrO2, Al2O3, CeO2, Nb2O5, La2O3, perovskite, or any mixture thereof. Doping excludes ferrous metasilicate fused with SiO2 at temperatures between 500°C and 2400°C.

[0006] In another embodiment, the present application relates to a method for the non-oxidative conversion of a hydrocarbon to hydrogen, the method comprising contacting a hydrocarbon with a catalyst under conditions to convert the hydrocarbon to hydrogen. The catalyst can be fused silica, quartz, glass, zeolite, Si3N4, SiC, SiC x O y (In the formula, 4x+2y=4), SiO a N b (where 2a+3b=4), a matrix comprising BN, TiO2, ZrO2, Al2O3, CeO2, Nb2O5, La2O3, perovskite, or any mixture thereof. A metal dopant is embedded in the matrix, where the metal dopant comprises Fe, Ni, Co, Cu, Zn, Mn, or any mixture thereof. The catalyst is not the product of fusing ferrous metasilicate with SiO2 at a temperature between 500°C and 2400°C.

[0007] These and other objects, features and advantages of the exemplary embodiments of the present disclosure will become apparent from the following detailed description of the exemplary embodiments of the present disclosure, taken in conjunction with the appended claims. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The following description of the embodiments provides non-limiting representative examples with reference to figures to particularly explain the features and teachings of different aspects of the present invention. It should be recognized that the described embodiments can be implemented alone or in combination with other embodiments different from the description of the embodiments. Those skilled in the art who review the description of the embodiments should be able to learn and understand the described aspects of the present invention that are different. The description of the embodiments should facilitate understanding of the present invention to the extent that other embodiments that are not specifically included but are within the knowledge of the person skilled in the art who reads the description of the embodiments are understood to be consistent with the application of the present invention.

[0009] Novel catalyst and method for preparing the catalyst The present application relates in one embodiment to novel catalysts for the non-oxidative conversion of hydrocarbons to hydrogen. The catalysts typically include a matrix and a metal dopant.

[0010] The matrix used in the catalyst can vary depending on the desired application, metal dopants, and / or other factors. Typically, the matrix is ​​fused silica, quartz, glass, zeolite, Si3N4, SiC, SiC x O y (In the formula, 4x+2y=4), SiO a N b (where 2a+3b=4), BN, TiO2, ZrO2, Al2O3, CeO2, Nb2O5, La2O3, perovskite, or any mixture thereof. As used herein, perovskite refers to any material that has a crystal structure similar to the mineral called perovskite. In some embodiments, perovskites have the chemical formula ABX3, where A and B are two cations of significantly different sizes, and X is an anion that bonds to both, such as oxygen.

[0011] The zeolite may be an MFI type zeolite, and / or may have a pore size of 4-20 Angstroms, and / or a Si / Al atomic ratio of 5-300.

[0012] The metal dopant is typically embedded in the matrix. The metal dopant includes Fe, Ni, Co, Cu, Zn, Mn, or any mixture thereof. In some embodiments, the embedded metal dopant includes isolated metal atoms that are substantially free of aggregates of size greater than 1 nm, and / or the embedded metal dopant includes an amount of isolated metal atoms that substantially reduces coking in the non-oxidative conversion of hydrocarbons, such as natural gas or methane, to hydrogen. The amount of isolated metal atoms is typically as high as reasonably possible, and in some embodiments may be greater than about 40% or greater than about 50% of all embedded metal dopants. The catalyst is typically not the product of fusing ferrous metasilicate with SiO2 at temperatures between 500°C and 2400°C.

[0013] Any suitable method can be used to produce the novel catalysts described above. Typically, suitable methods include doping a matrix material with a metal, the metal including Fe, Ni, Co, Cu, Zn, Mn, or any mixture thereof, and the matrix including fused silica, quartz, glass, zeolite, Si3N4, SiC, SiC x O y (In the formula, 4x+2y=4), SiO a N b (where 2a+3b=4), BN, TiO2, ZrO2, Al2O3, CeO2, Nb2O5, La2O3, perovskite, or any mixture thereof.

[0014] Doping can be accomplished in a number of different ways, the choice of which can depend on available equipment, materials, desired catalyst, and other factors.

[0015] In one embodiment, the doping includes ball milling the matrix material with one or more of SiO2, BO3, Fe2O3, or a mixture thereof to form a ball milled product, fusing the ball milled product to form a molten state and then cooling to form a cooled product, acid leaching the cooled product to remove at least a substantial portion of the agglomerated metals, and drying the acid leached product to form the catalyst.

[0016] In another embodiment, the doping comprises forming a gel. The process of forming the gel comprises combining a liquid source for matrix formation with an inorganic metal salt or inorganic metal alkoxide and hydrolyzing to form a gel. The gel can be dried, fused, and acid leached to remove at least a substantial portion of the aggregated metal. Further drying may be used to form the catalyst.

[0017] In another embodiment, the doping comprises fusing the metal-containing zeolite, acid leaching the fused metal-containing zeolite to remove at least a substantial portion of the agglomerated metals, and drying the acid leached fused metal-containing zeolite to form the catalyst.

[0018] In another embodiment, doping includes inserting a desired metal into silanol nests in a silica matrix, fusing the metal to the matrix, acid leaching the fused metal matrix, and drying the acid leached fused metal matrix to form the catalyst.

[0019] In another embodiment, the doping comprises subliming an organometallic precursor onto the high surface area dehydroxylated silica to form a single-site iron product, fusing metal to the single-site iron product, acid leaching the fused metallic single-site iron product, and drying the acid leached fused metallic single-site iron product to form the catalyst.

[0020] In another embodiment, the doping comprises washcoating a monolith catalyst support, where the monolith comprises a ceramic, silica, quartz, glass, metal, silicon carbide, silicon nitride, boron nitride, metal oxide, or any combination thereof, fusing a metal to the washcoated monolith catalyst support, acid leaching the fused, washcoated monolith catalyst support, and drying the acid leached, fused, washcoated monolith catalyst support to form the catalyst. The metal oxide may be selected depending on the desired catalyst and properties and may include titania, iron oxide, zirconia, mixed metal oxides, or any combination thereof. In some embodiments, the catalyst is melted to form an amorphous fused catalyst, and the amorphous fused catalyst is then shaped to obtain a desired shape, such as, for example, a honeycomb monolith or a cylinder.

[0021] Process for the non-oxidative conversion of hydrocarbons to hydrogen using novel catalysts The catalysts described above can be used, for example, in a process for the non-oxidative conversion of a hydrocarbon, such as natural gas, to produce hydrogen and potentially other products. The process generally involves contacting a hydrocarbon, such as natural gas, with the catalysts described above and / or a mixture of catalysts that includes one of the catalysts described above. The contacting is typically carried out under conditions that convert the hydrocarbon to hydrogen. The process may also produce light hydrocarbon products, such as ethylene, benzene, naphthalene, or any mixture thereof.

[0022] In the above specification, various embodiments have been described with reference to the accompanying drawings. However, it will be apparent that various modifications and changes can be made and additional embodiments can be implemented without departing from the broader scope of the invention as set forth in the following claims. The specification and drawings are therefore to be regarded in an illustrative sense rather than a restrictive sense.

[0023] example The following examples are offered by way of specific illustration and are not meant to be limiting.

[0024] Example 1 0.25%Fe / SiO2 catalyst 0.18 g of Fe(NO3)3·9H2O and 10 g of industrial grade silica gel with pore size of 60 Å and particle size of 40-63 μm were mixed and subjected to ball milling at 400 rpm for 12 h under air. The mixture was then pressed into pellets with a die set using a hydraulic press and then calcined at 550 °C in air. After sizing to 20-40 mesh, the final catalyst was obtained.

[0025] Example 2 0.5%Fe / SiO2 catalyst 0.36 g Fe(NO3)3·9H2O and 10 g silica gel (high purity grade Davisil grade 643, 150 Å, 200-425 mesh) were mixed and ball milled in air at 400 rpm for 12 h. The mixture was then pressed into pellets using a hydraulic press die set and then calcined in air at 700 °C. The resulting sample was crushed, sieved to 100-200 mesh, and leached in aqueous HNO3 (1 mol / L) at 60 °C for 5 h. The leached sample was dried at 130 °C overnight. The final Fe loading was 0.37%.

[0026] Example 3 0.5%Fe / TiO2 catalyst (sample c) The catalyst was prepared by impregnation method. 10 g of TiO2 (HOMBIKAT 8602, Venator) was mixed with 0.36 g of Fe(NO3)3·9H2O dissolved in 10 g of deionized water and then aged for 24 h. The mixture was then dried at 130 °C for 5 h. Finally, the material was calcined at 550 °C for 4 h. The obtained sample was crushed, sieved to 100-200 mesh, and then leached in aqueous HNO3 (1 mol / L) at 60 °C for 5 h. The leached sample was dried at 130 °C overnight. The final Fe loading was 0.13%.

[0027] Example 4 BaCe 0.9 Fe 0.07 Co 0.03 O3 Catalyst 0.1 mol BaO2, 0.9 mol CeO2, 0.07 mol FeO, and 0.01 mol Co3O4 were mixed and subjected to ball milling at 400 rpm for 24 hours under air. The mixture was then pressed into pellets using a hydraulic press die set and then calcined at 1000°C for 8 hours in air. The calcined sample was crushed and subjected to ball milling at 400 rpm for another 24 hours under air, then pressed into pellets and calcined at 1000°C for another 8 hours in air. After sizing to 40-60 mesh, the final catalyst was obtained.

[0028] Example 5 20%Zn / SiC catalyst 40.5 g of ZnO, 100 g of SiC, and 10 g of deionized water were mixed and subjected to ball milling under air at 450 rpm for 4 hours, the mixture was filtered and dried at 130° C. for 4 hours to produce the final catalyst.

[0029] Example 6 1%Ni / Al2O3 catalyst 2000 g of Al2O3 (Sasol PURALOX TH 100), 100 g of Ni(NO3)2·6H2O, and 1600 g of deionized water were blended in a Littleford mixer at 60 °C for 9 h. The mixture was dried at 130 °C and then calcined at 600 °C for 2 h.

[0030] Example 7 0.75%Fe / SiO2 catalyst 0.11 g of Fe2O3 and 10 g of industrial grade silica gel with pore size of 60 Å and particle size of 40-63 μm were mixed and subjected to ball milling under air at 400 rpm for 12 h. The mixture was then pressed into pellets with a die set using a hydraulic press and then calcined at 1700 °C in N2. After sizing to 20-40 mesh, the final catalyst was obtained.

[0031] Example 8 0.8%Fe / SiO2 catalyst The catalyst was prepared using a sol-gel method: 51.6 g of tetraethoxysilane (TEOS) was mixed with 662 mg of Fe(NO3)3·9H2O in 48 g of aqueous nitric acid (15 wt%) and 8 mL of ethanol, then stirred at 50 °C for 4 h. The resulting gel was first dried in air at 130 °C for 3 h and then heated in N2 at 1700 °C for 2 h.

[0032] Example 9 Catalyst Testing The catalysts prepared in Examples 1-8 were tested for the non-oxidative conversion of methane to hydrogen. The run conditions included a temperature of 1080° C. in a feed gas containing 90% CH4 / 10% N2 at a total flow rate of 120 mL / min under ambient pressure. The results of the catalytic tests are reported in Table 1. [Table 1]

Claims

1. 1. A catalyst for the non-oxidative conversion of hydrocarbons to hydrogen, comprising: Fused silica, quartz, glass, zeolite, Si 3 N 4 , SiC, SiC x O y (In the formula, 4x+2y=4), SiO a N b (in the formula, 2a+3b=4), BN, TiO 2 , ZrO 2 , Al 2 O 3 , CeO 2 , Nb 2 O 5 , La 2 O 3 a matrix comprising a zeolite, a perovskite, or any mixture thereof; a metal dopant embedded in said matrix, said metal dopant comprising Fe, Ni, Co, Cu, Zn, Mn, or any mixture thereof; Including, However, ferrous metasilicate is converted to SiO at temperatures between 500°C and 2400°C. 2 It is not a product fused with catalyst.

2. 10. The catalyst of claim 1, wherein the embedded metal dopant comprises isolated metal atoms that are substantially free of agglomerates.

3. 10. The catalyst of claim 1, wherein the embedded metal dopant comprises a quantity of isolated metal atoms that substantially reduces coking in the non-oxidative conversion of hydrocarbons to hydrogen.

4. A method for preparing a catalyst, comprising the steps of: doping the matrix material with a metal, said metal comprising Fe, Ni, Co, Cu, Zn, Mn, or any mixture thereof; Including, The matrix may be fused silica, quartz, glass, zeolite, Si 3 N 4 , SiC, SiC x O y (In the formula, 4x+2y=4), SiO a N b (in the formula, 2a+3b=4), BN, TiO 2 , ZrO 2 , Al 2 O 3 , CeO 2 , Nb 2 O 5 , La 2 O 3 , perovskite, or any mixture thereof; However, the doping step involves converting ferrous metasilicate into SiO at a temperature of 500°C to 2400°C. 2 and fusing is excluded, method.

5. The doping step comprises: The matrix material is SiO 2 , B 2 O 3 , Fe 2 O 3 or a mixture thereof to form a ball milled product; fusing the ball milled product to form a molten state and then cooling to form a cooled product; acid leaching the cooled product to remove at least a substantial portion of the agglomerated metal; drying the acid leached product to form the catalyst; The method of claim 4 , comprising:

6. The doping step comprises: forming a gel, said process of forming the gel comprising: combining said liquid source for matrix formation with an inorganic metal salt or an inorganic metal alkoxide; and hydrolyzing to form said gel. forming a gel comprising: drying the gel; and fusing the dried gel; and acid leaching the fused, dried gel to remove at least a substantial portion of the agglomerated metal; drying the acid leached, fused and dried gel to form the catalyst; The method of claim 4 , comprising:

7. The doping step comprises: fusing the metal-containing zeolite; acid leaching the fused metals-containing zeolite to remove at least a substantial portion of the agglomerated metals; drying the acid leached fused metal-containing zeolite to form the catalyst; The method of claim 4 , comprising:

8. Doping is inserting said metal into silanol nests within a silica matrix; fusing a metal to the matrix; acid leaching the fused metal matrix; drying the acid leached fused metal matrix to form the catalyst; The method of claim 4 , comprising:

9. The doping step comprises: subliming an organometallic precursor onto high surface area dehydroxylated silica to form a single-site iron product; fusing metal to the single-site iron product; acid leaching the fused metallic single-site iron product; drying said acid leached fused metallic single-site iron product to form said catalyst; The method of claim 4 , comprising:

10. The doping step comprises: washcoating a monolith catalyst support, the monolith comprising ceramic, silica, quartz, glass, metal, silicon carbide, silicon nitride, boron nitride, metal oxide, or any combination thereof; fusing a metal to the washcoated monolith catalyst support; acid leaching the fused, washcoated monolith catalyst support; drying the acid leached, fused and washcoated monolith catalyst support to form the catalyst; The method of claim 4 , comprising:

11. The method of claim 10 , wherein the metal oxide comprises titania, iron oxide, zirconia, mixed metal oxides, or any combination thereof.

12. 11. The method of claim 10, further comprising melting the catalyst to form an amorphous molten catalyst and shaping the amorphous molten catalyst to obtain a desired shape.

13. The method of claim 12 , wherein the desired shape comprises a honeycomb monolith.

14. The method of claim 12 , wherein the desired shape comprises a cylinder.

15. 1. A process for the non-oxidative conversion of hydrocarbons to hydrogen, comprising: contacting said hydrocarbon with a catalyst under conditions to convert said hydrocarbon into hydrogen; Including, The catalyst is Fused silica, quartz, glass, zeolite, Si 3 N 4 , SiC, SiC x O y (In the formula, 4x+2y=4), SiO a N b (in the formula, 2a+3b=4), BN, TiO 2 , ZrO 2 , Al 2 O 3 , CeO 2 , Nb 2 O 5 , La 2 O 3 a matrix comprising a zeolite, a perovskite, or any mixture thereof; a metal dopant embedded in said matrix, said metal dopant comprising Fe, Ni, Co, Cu, Zn, Mn, or any mixture thereof; Including, However, the catalyst converts ferrous metasilicate into SiO at a temperature of 500°C to 2400°C. 2 It is not a product fused with method.

16. 16. The method of claim 15, further comprising producing a light hydrocarbon product.

17. 17. The method of claim 16, wherein the light hydrocarbon products comprise ethylene, benzene, naphthalene, or any mixture thereof.

18. The method of claim 15 , wherein the hydrocarbon comprises natural gas.

19. 16. The method of claim 15, wherein the zeolite is an MFI type zeolite.

20. 16. The method of claim 15, wherein the zeolite comprises a pore size between 4 angstroms and 20 angstroms.

21. 16. The method of claim 15, wherein the zeolite has a Si / Al atomic ratio of 5 to 300.